Determining the role of pay later and hedonic motivation toward customer satisfaction mediated by impulsive buying - Ahmad Dzul Ilmi Syarifuddin; Rusnaena; Melinda Yunos; M. Faqih Naufal; Putri Amalia Ramadani (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
This study examines the impact of e-commerce pay-later adoption and hedonic shopping motivation on customer satisfaction, focusing on the mediating role of impulsive buying behavior in e-commerce. The research aims to understand how deferred payment services and pleasure-driven shopping motivations influence satisfaction levels, particularly through unplanned purchasing. Data was collected from e-commerce users and analyzed to assess the direct and indirect effects of pay-later services and hedonic motivations on satisfaction. The findings reveal that while Pay Later services offer convenience and flexibility, they decrease customer satisfaction by promoting impulsive buying, which often leads to financial strain and post-purchase regret. In contrast, hedonic shopping motivation does not directly affect customer satisfaction or does so through impulsive buying. This suggests that although consumers may shop for pleasure, this motivation alone is insufficient to sustain long-term satisfaction. The study contributes to the consumer behavior literature by highlighting the potential drawbacks of deferred payment options, questioning the paradoxical application of the Technology Acceptance Model (TAM) to E-Commerce BNPL, and challenging the linearity typically assumed in consumer behavior models. The findings underscore the importance of e-commerce platforms and Pay Later providers implementing strategies that mitigate impulsive buying, fostering more sustainable and satisfying shopping experiences. This research provides valuable insights for marketers and policymakers aiming to improve customer satisfaction within digital shopping environments.